Enzymatic Synthesis of Flavours and Fragrances, Antioxidants and Antimicrobials on the Example of Benzyl Alcohol and Its Selected Derivatives - Bartłomiej Zieniuk; Karina Jasińska; Katarzyna Wierzchowska; Agata Fabiszewska (Biology and Life Sciences Forum, 2022)
The aim of the work was the enzymatic synthesis of flavours and fragrances, antioxidants and antimicrobials with the use of benzyl alcohol and its selected derivatives via transesterification with vinyl acetate. The conversion yields of esters were dependent on the structure of alcohols and ranged from about 17% (4-hydroxybenzyl acetate) to approximately 90% (benzyl acetate). The performed reactions allowed the creation of esters with pleasant odours, such as benzyl, 4-methoxybenzyl, and piperonyl acetates. Furthermore, vanillyl acetate was proven to be the best antioxidant with the IC50 value of 0.83 ± 0.04 mM. In the reference to antimicrobial activity the largest inhibition zone diameters were determined for 2-hydroxybenzyl acetate and the values obtained against E. coli PCM 2057 were 19.0 ± 1.0 mm and 20.3 ± 0.6 in the case of S. aureus PCM 2054.